Appraisal : reducing control, enhancing effectiveness : a thesis submitted in partial fulfilment of the requirements for the degree of Ph. D. in Education at Massey University, Albany Campus, Auckland, New Zealand - Piggot-Irvine, Eileen (Massey University, 2001)
Between 1995 and 1999 the Ministry of Education (MoE) tightened the requirements for appraisal in schools in New Zealand (NZ). The first of three parts of the thesis reports on the impact of this tightening and enhanced control. The results from this impact study showed little indication of outcomes often associated with enhanced control such as increased defensiveness, decreased internal commitment, increased compliance, and inconsistent adoption of initiatives in appraisal. The results demonstrated an overall positive impact on appraisal implementation in schools associated with the enhanced control. On the downside, the results also provided a strong indication that much of the training conducted for appraisal had largely been superficial, and had failed to help appraisers to deal with problems with appraisees. These results led me to clarify 'effectiveness' in appraisal training, and to determine how such training could help appraisers and appraisees to establish educative appraisal interactions. Such interactions lead to effective outcomes in terms of resolving problems, and consequently improved teaching and learning. The theory, philosophy, guiding values and strategies of productive reasoning were refined and adapted to underpin the development of two approaches to training in problem confronting and resolution: one short-term (one day of training fitting national training allocation for approximately 219 appraisers in 25 secondary schools), and one long-term (an action research approach with five appraisers in one school). My implementation of these training interventions, and their evaluation, determined the second and third phases reported on in this thesis. For Intervention #1 (the short-term training), the evaluation results showed a considerable gap between appraiser espousals of educative process implementation and their practice. This became particularly evident when the majority of appraisers reported that the training had helped them to be more open and to deal with, rather than avoid, problems with appraisees, and yet the closer examination of their interactions with appraisees, and appraisee feedback, revealed little employment of an educative process. Intervention #2 (the longer-term training), was designed to enable appraisers to better understand and further internalise the educative process, to provide further opportunities for practice, and provide more extensive follow-up support from myself and other appraisers. Although the intended action research approach, the Problem Resolving Action Research (PRAR) Model, was only partially realised in this intervention, the evaluation results led me to conclude that for three of the five appraisers a considerable positive shift in implementation of educative process skills occurred. These results indicated that the elements contributing to this shift included: appraiser commitment to improvement (for both themselves as appraisers, and for the teachers they were appraising); consciousness-raising associated with exposure of the espousal-practice gap; extended support; and the opportunity to repeat learning. The research also highlighted, and confirmed, the importance in action research of: gaining ownership and commitment; enhancing collaboration, and mutually informing theory and practice. Overall, this thesis provides rare evidence to demonstrate that, given appropriate training, appraisal can ultimately improve teaching and learning.
Keywords: Teachers; In-service training; Rating of; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education